2017
DOI: 10.17161/jas.v3i3.6518
|View full text |Cite
|
Sign up to set email alerts
|

Family Relationships and Youth Sport: Influence of Siblings and Parents on Youth's Participation, Interests, and Skills

Abstract: Taking a family systems perspective, the present study investigated how older siblings' and parents' (mothers' and fathers') self-reported interests, skills, and participation in sports predicted younger siblings' attitudes and behaviors in those same domains. Testing social learning principles, we further examined whether family members' influence was stronger when they shared warmer relationships and siblings shared the same gender. Participants included mothers, fathers, and adolescent-aged first and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Researchers recently have begun to explore the roles of siblings in sport (see Blazo & Smith, 2018). Examples of this work include the experience of having an athletically gifted sibling in the household (Blazo et al, 2014;Newhouse-Bailey et al, 2015) and socialization into and continued involvement in sport (e.g., Osai & Whiteman, 2017;Ziviani et al, 2006). Results of this work suggest that young athletes engage in sibling processes such as modeling and differentiation that shape their sport-related behaviors, attitudes, experiences, and outcomes.…”
Section: The Youth Sport System 10mentioning
confidence: 99%
“…Researchers recently have begun to explore the roles of siblings in sport (see Blazo & Smith, 2018). Examples of this work include the experience of having an athletically gifted sibling in the household (Blazo et al, 2014;Newhouse-Bailey et al, 2015) and socialization into and continued involvement in sport (e.g., Osai & Whiteman, 2017;Ziviani et al, 2006). Results of this work suggest that young athletes engage in sibling processes such as modeling and differentiation that shape their sport-related behaviors, attitudes, experiences, and outcomes.…”
Section: The Youth Sport System 10mentioning
confidence: 99%
“…The influence of older siblings helps younger siblings to improve their skills and abilities. 33,34 This is because younger siblings have a strong desire to catch up with their older siblings 32 and, as Hopwood et al 28 highlighted, need to develop creativity, decision-making skills, and tactical intelligence to win. If an environment can be created such that the first child can continue to play football without leaving the sport, the number of first-born children will increase and become equal to or exceed that of second-born children, approaching a Poisson (uniform) distribution and eliminating the problem of second-born child dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Influence from older siblings also helps younger siblings improve their skills and abilities. 33,34 Simultaneously, a sibling can have a negative effect. For example, in rugby, younger brothers receive statistically more yellow cards during a game than older brothers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have considered the role of siblings across sport participation (i.e., participation, development, and performance), suggesting that siblings can have a meaningful influence on an athlete in both a positive and negative way (Côté, 1999 ; Davis and Meyer, 2008 ; Blazo et al, 2014 ; Trussell, 2014 ; Hopwood et al, 2015 ; Allbaugh et al, 2016 ; Nelson and Strachan, 2017 ; Osai and Whiteman, 2017 ; Taylor et al, 2017 , 2018 , 2021 ). Reflecting this polar influence, an initial retrospective study by Côté ( 1999 ) investigated the historical family dynamics of four 18-year old elite junior level athletes throughout their developmental years.…”
Section: Reviewing Characteristics Of the Sibling Relationshipmentioning
confidence: 99%
“…Similarly to previous qualitative studies, this research revealed the positive older sibling influence on psychological and social factors. Subsequent qualitative studies by Osai and Whiteman ( 2017 ) and Nelson and Strachan ( 2017 ) explored the potential impact of siblings on TD. Both studies attributed siblings' active engagement to the enhancement of skills and abilities.…”
Section: Reviewing Characteristics Of the Sibling Relationshipmentioning
confidence: 99%